2014
DOI: 10.1149/2.014408jes
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of Reduction Mechanisms of Ethylene Carbonate and Fluoroethylene Carbonate on Li+-Adsorbed Si Clusters

Abstract: Silicon anodes show great potential but have severe practical limitations resulting from swelling effects during lithiation and from solid-electrolyte interphase (SEI) layers formed at the electrode surface due to electrolyte electrochemical instability. Aiming to understand the anode SEI reactions at ultra-low degrees of lithiation, we investigate reductive decomposition mechanisms of ethylene carbonate (EC) and fluoroethylene carbonate (FEC) on Li + -adsorbed Si clusters using density functional theory. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 57 publications
3
69
0
Order By: Relevance
“…Leung and Budzien compared EC decomposition on the basal plane of lithiated graphite (LiC 6 ), terminated with =O, -OH and -H and found that C = O edges provide a larger driving force for EC reduction 62 The observation that EC is more inclined to decompose in the presence of oxygen/ hydroxyl termination is consistent with other simulation results. 96 Besides graphite, EC decomposition was simulated on Li, 57,60,97 Si, 45,64,98 and Sn 99 electrodes as well. Due to the lower potential of Li metal than graphite, the decomposition of EC on Li metal is spontaneous and much faster than that on LiC 6 surfaces.…”
Section: Ec Solvent Decomposition Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Leung and Budzien compared EC decomposition on the basal plane of lithiated graphite (LiC 6 ), terminated with =O, -OH and -H and found that C = O edges provide a larger driving force for EC reduction 62 The observation that EC is more inclined to decompose in the presence of oxygen/ hydroxyl termination is consistent with other simulation results. 96 Besides graphite, EC decomposition was simulated on Li, 57,60,97 Si, 45,64,98 and Sn 99 electrodes as well. Due to the lower potential of Li metal than graphite, the decomposition of EC on Li metal is spontaneous and much faster than that on LiC 6 surfaces.…”
Section: Ec Solvent Decomposition Mechanismmentioning
confidence: 99%
“…When Si becomes lithiated, its voltage drops, and therefore the lithium concentration in silicon greatly influences the electrolyte reduction reactions. 53,64,98,99 Martinez de la Hoz et al 64 found that EC can be reduced by two different twoelectron mechanisms (one simultaneous and one sequential) on intermediately lithiated silicon surfaces (LiSi). A later work done by Ma and Balbuena 98 provided a more detailed reduction mechanism of EC under the low lithiated state of silicon anode.…”
Section: Ec Solvent Decomposition Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…It will be shown that FEC nearly suppresses the reduction of any other electrolyte component, which is consistent with the previous literature and suggests that the rate of FEC reduction is greater than the reduction of EC and linear carbonates. [26][27][28][29][30][31] Furthermore, due to the continuous consumption of FEC quantified by 19 F-NMR, the number of charge/discharge cycles over which silicon anodes can by stabilized by FEC is directly proportional to the total moles of FEC per …”
mentioning
confidence: 99%
“…For instance, the results presented in Figure 2 and Table III indicate that FEC may be consumed through reactions with generated lithium alkoxides. In a recent publication, Ma et al 80 also showed using DFT calculations that FEC may be reduced following 2-electron reduction pathways that do not generate gaseous products. In their calculations, they showed that FEC may readily be reduced at the surface of Si clusters with a low lithiation state following pathways with very low energy barriers.…”
mentioning
confidence: 99%